Impact of school culture on student aspirations - Song, Peggy. (2008)
The primary aim of this research is to examine, compare and contrast students and teachers’ perceptions of the different aspects of school culture conditions, identified in the research done by the National Centre for Student Aspirations ( a leader in the field of student aspirations in New England of the United States of America). This study also aims to identify the school cultural conditions that may promote student aspirations.